Declassified intelligence satellite imagery as a tool to reconstruct past landforms and surface processes: The submerged riverscape of the Tigris River below the Mosul Dam Lake, Iraq. Issue 10 (13th May 2022) - Forti, Luca; Mariani, Guido S.; Brandolini, Filippo; Pezzotta, Andrea; Zerboni, Andrea
Abstract: Located along the Tigris River in the Kurdistan Region of Iraq, the Mosul Dam Reservoir is the second biggest dam of the Near East and represents an important water storage for local human activities. The dam was built between 1981 and 1988 north of the village of Eski Mosul, submerging the course of the Tigris River for c. 100 km. The analysis of historical images derived from declassified Corona satellite imagery acquired between December 1967 and August 1968 reveals the pristine pattern of the Tigris River, including the seasonal changes of its riverbed, shifting across the hydrological year from meandering to anastomosing patterns. Geomorphological mapping based on Corona images allowed us to estimate the seasonal modification of fluvial elements such as the floodplain and point, middle and longitudinal bars. The comparison with Landsat data collected since the 1990s showed the first phases of the basin filling and the control on the present‐day aspect of the lake inherited from the setting of the Tigris channel belt and, more in general, the litho‐structural control over the evolution of the local hydrographic network; we also document the influence of the original Tigris River course on its recent insertion into the lake. Our work allowed reconstruction of the ancient fluvial landscape below the Mosul Dam Lake and the evolution of its riverscape controlled by litho‐structural factors and seasonal variations of the river discharge. Finally, this contribution highlights the relevance of declassified intelligence satellite imagery in interpreting natural geomorphic processes and landforms, today altered by human agency. Abstract : Historical images derived from declassified Corona satellite imagery acquired between December 1967 and August 1968 reveal the pristine pattern of the Tigris River Geomorphological mapping based on Corona images allowed to estimate the seasonal modification of fluvial elements. Timelapse of Landsat imagery showed the first phases of the basin filling and the control on the present‐day aspect of the lake.